Penguatan Branding dan Pemasaran Digital pada UMKM Warung “Mbak Raisha” di Pantai Karang Jahe, Kabupaten Rembang - Muhammad Kholilur Rohman; Aelia Rara Dianti; Siti Utami; Dian Anita Sari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Karang Jahe Beach is one of the leading tourism destinations located in Rembang Regency. This area provides a great opportunity for Micro, Small, and Medium Enterprises (MSMEs) to develop and reach a wider market. One of the MSMEs in this area is Warung "Mbak Raisha" owned by Mrs. Inayah which has been operating since 2015. This stall is engaged in providing food and beverages for tourists. However, these MSMEs face various challenges in managing their business, including the lack of digital financial records, the lack of social media accounts as a means of digital promotion, the lack of a business logo, and the management of orders and product packaging that is not optimal. This condition causes limitations in terms of competitiveness, management efficiency, and marketing reach which has an impact on overall business growth and hinders the potential for future business development. Community service activities are carried out to help overcome these problems through strategies to strengthen branding and digital marketing. Some of the concrete steps taken are the creation of a logo as a brand identity, the installation of banners as a visual identity of the business, training on the use of social media (Instagram) as a means of promotion, the preparation of price lists, and digital financial recording using simple applications. In addition, education was also provided regarding the importance of attractive packaging to increase the selling value of products. The results of the mentoring show that Warung "Mbak Raisha" now has a stronger business identity, a more targeted promotion system, and more efficient management. This effort is expected to be able to encourage business growth and make MSMEs better prepared to face business challenges in the digital era.